2006
DOI: 10.1038/oby.2006.259
|View full text |Cite
|
Sign up to set email alerts
|

A Workplace Intervention to Promote Stair Climbing: Greater Effects in the Overweight

Abstract: EVES, FRANK F., OLIVER J. WEBB, AND NANETTE MUTRIE. A workplace intervention to promote stair climbing: greater effects in the overweight. Obesity. 2006; 14:2210 -2216. Objective: Stair climbing is a lifestyle physical activity that uses more calories per minute than jogging. This study tested an intervention designed to promote stair climbing in a workplace. Because previous studies provide only equivocal evidence of the effects of increased stair climbing in worksites, a formal comparison of the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 28 publications
5
87
1
Order By: Relevance
“…?"). 33 Interview work indicates that this approach is more likely to motivate stair choice than generic entreaties to be active (eg, "Regular stair climbing helps to keep you active"). 34 Eves et al's intervention persuaded an extra 2.5% of 'normal weight' individuals to climb the stairs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…?"). 33 Interview work indicates that this approach is more likely to motivate stair choice than generic entreaties to be active (eg, "Regular stair climbing helps to keep you active"). 34 Eves et al's intervention persuaded an extra 2.5% of 'normal weight' individuals to climb the stairs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 2 methodologically-robust studies have demonstrated effects of weight status on stair climbing. 19,33 In addition, the physical characteristics of the setting may be important. A recent audit of university faculty buildings identified 10 spatial variables which influenced stair use (eg, stair width).…”
Section: Discussionmentioning
confidence: 99%
“…For example, open and accessible stairwells and on-site physical activity facilities at worksites increased the physical activity of employees. 115,116 …”
Section: Modifying the Workplace To Encourage Positive Behavior Changementioning
confidence: 99%
“…29 In the latter study, a significant effect on stair climbing (ascent) was seen (OR 1.12, p<0.005). Kerr et al 30 reported no significant intervention effect for stair climbing, but there was a significant increase in stair descent (OR 1.21, 95% CI 1.07 -1.37).…”
Section: Discussionmentioning
confidence: 77%